The Effect of Product Standards on Agricultural Exports from Developing Countries - Ferro, Esteban; Wilson, John S.; Otsuki, Tsunehiro (World Bank, Washington, DC, 2013)
The authors create a standards restrictiveness index using newly available data on maximum residue levels of pesticides for 61 importing countries. The paper analyzes the impact that food safety standards have on international trade of agricultural products. The findings suggest that more restrictive standards are associated, on average, with a lower probability of observing trade. However, after controlling for sample selection and the proportion of exporting firms in a gravity model, the analysis finds that the effect of standards on trade intensity is indistinguishable from zero. This is consistent with the assumption that meeting stringent standards increases primarily the fixed costs of exporting. Once firms enter the market, however, standards do not impact the level of exports. The analysis also finds a greater marginal effect of BRICS (Brazil, Russia, India, China, and South Africa) standards on the probability of trade, relative to other countries' standards, keeping in mind however that on average BRICS standards are less restrictive. The analysis also suggests that exporters in low-income countries are more adversely affected by stricter standards.